2014
DOI: 10.18596/jotcsa.10054
|View full text |Cite
|
Sign up to set email alerts
|

Microwave assisted synthesis of some halosubstituted chalcones

Abstract: An efficient microwave-assisted synthesis of halosubstituted chalcones were presented by the condensation of halosubstituted ketones and substituted aldehydes. These reactions were found to be economically cheap in comparison with classical synthesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…In view of applications of chalcones and in continuation of our previous works reported on green synthetic protocol towards synthesis of bioactive compounds, [24][25][26][27] we synthesized new class of benzyloxy chalcone derivatives (3a-3h) under the condition of microwave assisted Claisen-Schmidt condensation of substituted aromatic aldehydes with 2-acetyl-1-naphthol/halosubstituted 2-acetyl-1naphthol in presence of KOH in good yield. 28 We found that microwave technique has several advantages including clean and easy work-up procedure, short reaction time, high yield and eco-friendliness.…”
Section: Synthesismentioning
confidence: 97%
“…In view of applications of chalcones and in continuation of our previous works reported on green synthetic protocol towards synthesis of bioactive compounds, [24][25][26][27] we synthesized new class of benzyloxy chalcone derivatives (3a-3h) under the condition of microwave assisted Claisen-Schmidt condensation of substituted aromatic aldehydes with 2-acetyl-1-naphthol/halosubstituted 2-acetyl-1naphthol in presence of KOH in good yield. 28 We found that microwave technique has several advantages including clean and easy work-up procedure, short reaction time, high yield and eco-friendliness.…”
Section: Synthesismentioning
confidence: 97%
“…Claisen-Schmidt condensation is the classical method in which aldehydes reacted with ketone in presence of aqueous alkaline bases 11 , barium hydroxide or Lithium hydroxide 12 . Chalcone synthesis also achieved by various methods by using microwave irradiation [13][14][15] , ultrasound irradiation 16 , grinding technique [17][18][19][20] , Suzuki reaction 21 and by using diverse catalyst like anhydrous K2CO3 9 , NaOH-Al2O3 1 , SOCl2 22 , KF / natural phosphate 23 , Potassium phosphate 24 , CaO, NH4OH 25 , Na2CO3 26 ,natural phosphate/lithium nitrate 27 , silica-sulphuric acid 28 ,Iodine 29 ,NaOH [30][31] and KOH 32 .…”
Section: Introductionmentioning
confidence: 99%